Evaluation of study methodology patterns among first year MBBS students: a pilot study - Bharati, Anup S.; Pawar, Yogesh; Samarth, Abhishek (International Journal of Research in Medical Sciences, 2021)
Background: Academic achievement and achieving educational goals require the existence of several factors, most importantly the study habits of individuals. Because of the high sensitivity of future professions, and the need for comprehensive learning of the curriculum, paying attention to the study habits and its promotion is critically important. The differences in study habits can be attributed to the individual differences and their previous educational background. Studies indicate that incorrect study habits of students need to be identified and fixed because many of these incorrect habits get transferred to higher education levels. Hence, it becomes necessary to provide suitable guidance to improve these habits. Methods: This was cross sectional, observational pre-validated questionnaire-based pilot study conducted by enrolling 107 students of first year MBBS. Results: The study included 46 males and 57 females and 4 did not mention the gender. Age of participants ranged from 17 years to 21. Around half students were from urban background, half of the students were from English medium. 57.9% participants reported they did not have a regular sleep pattern and 12.15 % reported they strongly never had regular sleep pattern. All students denied regular exercise. 41 out of 107 said they use or used cigarettes to boost their concentration and memory. On the other hand, 42.9% said they used alcohol and other substances in the past. When compared by gender difference, males were more likely to engage in day dreaming, and skip chapter that does not interest them as compared to female participants. Females were more likely to make an outline of chapters before reading, refer dictionary when needed, discuss studied topic with others by asking questions. Surprisingly female were more embarrassed of asking questions. Conclusions: To conclude, the results of our study on medical students showed that attending study skill workshops and learning related abilities can empower the students in the areas of selecting the main idea, study aids, information processing, self-testing, and use of test strategies. However, teaching self-regulation strategies and practicing them in class can create opportunities that help the students manage and monitor their learning.